Selective Modulators of PPAR-γ Activity: Molecular Aspects Related to Obesity and Side-Effects - Fang Zhang; Brian E. Lavan; Francine M. Gregoire (PPAR Research)
Peroxisome proliferator-activated receptor γ (PPAR-γ) is a key regulator of lipid metabolism and energy balance implicated in the development of insulin resistance and obesity. The identification of putative natural and synthetic ligands and activators of PPAR-γ has helped to unravel the molecular basis of its function, including molecular details regarding ligand binding, conformational changes of the receptor, and cofactor binding, leading to the emergence of the concept of selective PPAR-γ modulators (SPPARγMs). SPPARγMs bind in distinct manners to the ligand-binding pocket of PPAR-γ, leading to alternative receptor conformations, differential cofactor recruitment/displacement, differential gene expression, and ultimately differential biological responses. Based on this concept, new and improved antidiabetic agents for the treatment of diabetes are in development. This review summarizes the current knowledge on the mechanism of action and biological effects of recently characterized SPPARγMs, including metaglidasen/halofenate, PA-082, and the angiotensin receptor antagonists, recently characterized as a new class of SPPARγMs.